Copyright Literacy and Copyright Education for Information Professionals - Todorova, Tania (Páginas a&b: arquivos e bibliotecas, 2020)
The paper positions the importance of copyright literacy and copyright education for information professionals. Based on a review of scientific literature, the meaning of the term “copyright literacy” is clarified and its characteristics are presented to be used in updating the educational content and methodology of teaching in academic education and continuing professional development training programs. Developing high levels of copyright literacy (knowledge, skills and behaviours) and the ability to implement institutional copyright policy is essential for LIS (Library and Information Science) and cultural heritage professionals. The proposed conclusions in the paper are based on: findings from a multinational survey on copyright literacy of specialists from libraries and other cultural institutions (2013-2015); summary of the activities of the International Copyright Literacy Group (ICLG) in the period 2012-2019; and review of the current documents such as IFLA Statement on Copyright Education and Copyright Literacy (2018) and Copyright in the Digital Single Market Directive (EU) 2019/790 of the European Parliament and of the Council (2019). Keywords: Copyright in the Digital Single Market Directive (EU); Copyright literacy; Copyright policy; International Copyright Literacy Group.